Utilization of Agricultural Wastes in the Manufacture of Composite Boards - P.M Macatangay; E.C Mangundayao; C.A.M Rosales (ASEAN Journal on Science and Technology for Development, 2012)
Development of useful composite materials out of agricultural waste has become a desirable option in recycling. This led to the production of composite boards being used in the construction industry. In this paper, three types of available agricultural wastes in the province of Batangas — peanut shells, corn husks and banana sheath — were independently utilized in the production of composite boards. The raw materials were either air or sun dried, then crushed (for peanut shells) and extracted (for banana sheath and corn husks) before mixing with the binder. Urea formaldehyde (UF) was used as binder for peanut shells and banana sheaths while cleaned used plastic bags were chopped and mixed with corn husks before subjecting to hot compress machine. For each mat, the followingproportions were used:1000 gm banana fibres, 500 gm of UF mixed with 250 gm of water; 720 gm of crushed peanut shells, 133 gm UF with 12% resin content; 40% corn husks, 60% plastic strips by weight. The physical and mechanical characteristics like modulus of rupture (MOR), internal bond, face screw head test (FSHT) or Nail Head Pull through (NHPT), water absorption and thicknessswelling were determined for each board and the results were compared to the values set by the Philippine National Standards (PNS). Based on statistical results, the corn husk-plastic composite boards conformed to all parameters in the PNS; the density, thickness swelling, IBS, and NHPT/ FSHT of peanut shell-resin composite boards conformed to the PNS; and the thickness swelling,density, MOR and NHPT/FSHT of the banana sheath-UF composite boards conformed to the PNS.